Uma plataforma para exploração da genealogia acadêmica brasileira - João Marcos Martins da Costa Cota (2021)
Throughout history, many researchers have made remarkable contributions to science, not only advancing knowledge, but also forming new scientists. Currently, identifying and studying the formation of researchers over the years is a challenging task, as the current repositories of theses and dissertations are cataloged in a decentralized manner in different digital libraries, many of them with limited scope. In this MSc dissertation, we take a first step towards building a large repository to record the Brazilian academic genealogy. For that, we collected data from the CNPq Lattes platform and developed a computational framework in order to generate the academic genealogy trees of Brazilian researchers from them, also providing additional data resulting from a series of analyses that describe the main properties of such trees. Our effort has identified interesting aspects related to the academic background of the Brazilian researchers, which highlight the importance of generating and cataloging their academic genealogy trees